Mezomorfne lastnosti 4-{omega-bis(2-hidroksietil)amino-alkoksi}-4'-metoksiazobenzenov - Brecl, Marko (Kovine zlitine tehnologije, 1999)
Liquid crystalline behavior of a series of 4{-omega-bis(2-hydroxyethil)amino-alkoxy}-4'-methoxyazobenzenes (CnOMe-diols) with even number of carbon atoms in the alkyl chain (n = 2, 4, 6, 8, 10 and 12) was characterized by means of differential scanning calorimetry and optical polarizing microscopy. C2OMe-diol did not exhibit a liquid crystalline behavior, while diols with n>4 form smectic mesophases. CnOMe-diols are suitable monomers for synthesis of the side chain liquid crystalline polyurethanes and polyesters and make possible the investigation of the influence of the spacer length on mesomorphic properties of side chain liquid crystalline polymers. Namely, they depend on molecular structure (the nature of the polymer backbone, the flexible spacer and the mesogenic unit), molar mass, polydispersity nad tacticity.
Keywords: smektični tekoči kristali; fazni prehodi; termična analiza